Prediksi Kadar Glukosa Darah Terhadap Mortalitas Pasien di RSUP H. Adam Malik Medan - Elsarika Damanik; Normi Parida Sipayung (LPPM Sekolah Tinggi Ilmu Kesehatan Siti Hajar Medan, 2019)
Introduction: Blood glucose levels are important in the human body because to support health so that they can do work activities properly. The initial action in patients with blood glucose levels who experience a head injury determines the outcome in the hospital. Patients who cannot maintain their blood glucose levels within the first 24 hours of treatment can cause a bad outcome, in the end, even increasing the mortality rate due to blood glucose levels. Aims: This study aims to analyze the predictions of blood glucose levels on patient mortality at H. Adam Malik Hospital in Medan. Methods: In this study, the authors used observational analytic with a retrospective cohort study design. The population in this study were all patients with high blood glucose levels who suffered head injuries in the Emergency Room (IGD) of H. Adam Malik Hospital in Medan and used purposive sampling so that 40 patients selected for high blood glucose levels with a head injury. Results: Based on the tabulation result using chi-square test shows that mortality was more prone to occur in patients who had blood glucose levels> 145 mg/dl with p-value 0.00 and odds ratio of 0.18. Conclusion: So in conclusion, a severe head injury patients who have blood glucose levels > 145 mg/dl are prone to death but do not deny mortality in patients who have blood glucose levels <145 mg/dl due to a severe head injury